Civic Insecurity Law, Order and HIV in Papua New Guinea - Luker, Vicki; Dinnen, Sinclair (State, Society and Governance in Melanesia, 2010)
Papua New Guinea has a complex 'law and order' problem and an entrenched epidemic of HIV. This book explores their interaction. It also probes their joint challenges and opportunities-most fundamentally for civic security, a condition that could offersome immunity to both. This book is a valuable and timely contribution to a limited but growing body of scholarship in the social and structural contexts of HIV epidemiology in Papua New Guinea. The volume offers a unique collection of interdisciplinary insights on the connections between law and order and the HIV epidemic and is presented in a manner accessible to a wide audience, scholars and lay people alike... Significantly, this is the first volume to critically examine the complex and inexorable links between HIV, gender, violence, and security within a theoretical framework thv at illuminates the challenges of the epidemic for PNG's future cohesion and stability as a young nation...The importance of this courageous book cannot be overstated. While it communicates an urgent and potent message about the need for immediate action ... it offers insightful reflections on the processes and possibilities of social transformation that undoubtedly will have enduring scholarly and practical value. Dr Katherine Lepani, Social Foundations of Medicine, The Australian National University.